2014
DOI: 10.1016/j.ijmachtools.2014.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Conservation law of surface roughness in single point diamond turning

Abstract: Carbon Fiber-Reinforced by Plastic (CFRP) is now commonly used in the aircraft industry. The main challenge is to manufacture this difficult-to-cut work material, considering its quality criteria and economical aspects. Drilling is the main machining operation required for the assembly of the aircraft structure. In this paper, results are presented and discussed regarding exit delamination studied at a local scale. Because of the anisotropic properties of CFRP, the fiber cutting modes change with the composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(34 citation statements)
references
References 20 publications
4
29
0
1
Order By: Relevance
“…This effect is more likely when using large tool nose radius in combination with small depths of cut and feed rates [39]. The combination of low depths of cut and feed rates leads to small undeformed chip thickness comparable to tool nose radius and, in this case, a part of the surface roughness values depends on the undeformed chip thickness [40]. Moreover, in Fig.…”
Section: Surface Roughnessmentioning
confidence: 92%
“…This effect is more likely when using large tool nose radius in combination with small depths of cut and feed rates [39]. The combination of low depths of cut and feed rates leads to small undeformed chip thickness comparable to tool nose radius and, in this case, a part of the surface roughness values depends on the undeformed chip thickness [40]. Moreover, in Fig.…”
Section: Surface Roughnessmentioning
confidence: 92%
“…Ng et al [83] investigated surface roughness in diamond cutting of aluminum 2075-T6 and found that the generated surface at an UCT smaller than the tool edge radius is rougher than that with larger UCT. The phenomenon that the cutting-induced surface roughness always deviates from the theoretical value could be partly attributed to the effect of the cutting tool edge [156]. The elastic recovery and the side flow of materials are two factors affected by tool edge and further influence the surface roughness.…”
Section: Influence On Surface Generationmentioning
confidence: 97%
“…Results showed that the elastic recovery for the sharp tool is lower than for the blunt tool and the variation of elastic recovery is in coherence with the change of surface roughness [160]. To predict the surface roughness in single point diamond turning, Zong et al [156] introduced an additional term to the roughness formulation proposed by Grezesik [161]. It is formulated as…”
Section: Influence On Surface Generationmentioning
confidence: 99%
See 2 more Smart Citations